Rabszolgavasar (I. es II. Rész) . Slave-Market – parts 1, 2 - Bódis, Kriszta (Inforg Stúdió, 2005)
Duration: 01:26:00 Slave Market is a documentary in two parts in which the viewers become familiar with the human market of prostitutes, the people who control them, and the clients. In Part 1, the viewers get to know a victim of a police scandal. The story happened three years ago but is unresolved even today. The life of the teenage girl sold into sexual servitude looks just as bleak. Part 2 is about young prostitutes who ended up in prison for several years after the law against prostitution was enforced. The film questions the stereotypes connected with prostitution.